Management of Language Tests at the Grade Level (Format, Rubric, Validity) - Abdullah, Agustin; Pateda, Lamsike; Kadir, Suleman (Language Development Center, 2022)
Background: Classroom-based language testing management is a complex pedagogical process integrating technical, ethical, and contextual considerations to ensure fair and meaningful assessment practices. This study emerges from the growing need to understand how teachers design, implement, and refine classroom assessments that balance objectivity, authenticity, and validity. Purpose: This research explores how teachers manage test formats, develop scoring rubrics, and maintain assessment validity through reflective and adaptive practices within diverse learning environments. Method: Employing a qualitative case study design, the research gathered data through in-depth interviews, classroom observations, and document analyses involving language teachers at the secondary school level. Results and Discussion: The findings reveal that effective classroom testing depends on teachers’ ability to harmonize objective and subjective assessment formats. Teachers used pilot testing and peer moderation to clarify instructions and standardize rubric interpretation, enhancing fairness and transparency. Adaptation of test formats based on learners’ linguistic abilities, learning styles, and sociocultural backgrounds further enriched the authenticity and inclusivity of assessment practices. Conclusions and Implications: classroom test management functions not merely as a measurement activity but as a reflective pedagogical practice that links assessment with learning improvement. This study contributes to theory by expanding the concept of integrated classroom assessment management. It offers practical insights for enhancing teachers’ assessment literacy in multilingual educational contexts.